The Influence of Compensation and Work Discipline on Employee Work Productivity at the Topshop Store in Bandar Lampung - Claudio Virginia Capello; Hendri Dunan (International Journal of Economics, Management and Accounting (IJEMA), 2024)
This research aims to determine the influence of Compensation and Work Discipline on Employee Work Productivity at the Topshop Store in Bandar Lampung. This type of research is quantitative. The data source used in this research is primary data through questionnaires distributed to Topshop Bandar Lampung store employees. This data collection method uses documentation and literature study. The population in this research is the Topshop Store in Bandar Lampung. The sampling method uses a purposive sampling technique. The data analysis method used in this research is the multiple linear regression analysis method using a statistical program, namely the Statistical Program For Social Science (SPSS). The results of this research show that when viewed from a significant level of 0.003 < 0.05, which means that Ha1 is accepted and rejects Ho1 which states that there is an influence of compensation on work productivity and a significant level of 0.001 < 0.05 which states that Ha2 is accepted and rejected Ho2 which states that there is an influence of work discipline on Work productivity.